2018
DOI: 10.1038/s41598-018-31168-0
|View full text |Cite
|
Sign up to set email alerts
|

Marchantia liverworts as a proxy to plants’ basal microbiomes

Abstract: Microbiomes influence plant establishment, development, nutrient acquisition, pathogen defense, and health. Plant microbiomes are shaped by interactions between the microbes and a selection process of host plants that distinguishes between pathogens, commensals, symbionts and transient bacteria. In this work, we explore the microbiomes through massive sequencing of the 16S rRNA genes of microbiomes two Marchantia species of liverworts. We compared microbiomes from M. polymorpha and M. paleacea plants collected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 69 publications
1
42
0
Order By: Relevance
“…Marchantia polymorpha and M. paleacea (Alcaraz et al 2018); both showed less diversity in their root analogs (bladders, and rhizoids) than their soil sources, supporting the two-step model. The Marchantia microbiomes even allowed us to perform an extreme microbial selection due to the in vitro propagation of these plants, highlighting a reduced core of closely related microbial inhabitants (Alcaraz et al 2018). Testing multiple plants, wild and domesticated, could reduce the gaps in understanding the microbiome structure loss as a domestication trade-off.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Marchantia polymorpha and M. paleacea (Alcaraz et al 2018); both showed less diversity in their root analogs (bladders, and rhizoids) than their soil sources, supporting the two-step model. The Marchantia microbiomes even allowed us to perform an extreme microbial selection due to the in vitro propagation of these plants, highlighting a reduced core of closely related microbial inhabitants (Alcaraz et al 2018). Testing multiple plants, wild and domesticated, could reduce the gaps in understanding the microbiome structure loss as a domestication trade-off.…”
Section: Discussionmentioning
confidence: 62%
“…The 16S rRNA protocol used in this work had been used previously and is detailed at GitHub (Alcaraz et al, 2018; https://genomica-fciencias-unam.github.io/SOP/). In summary, gene amplicon libraries were quality inspected using Fastx Toolkit (http://hannonlab.cshl.edu/fastx_toolkit/) and trimmed to a 250 bp length.…”
Section: S Rrna Gene Amplicon Sequence Analysismentioning
confidence: 99%
“…We used a previously reported protocol for 16S rRNA gene amplicons analysis 34 , which is detailed at GitHub (https://genomica-fciencias-unam.github.io/SOP/). Briefly, sequencing pair-ended reads were merged, using a minimum of 470 bp, a 15 bp of minimum overlapping, and with a quality threshold of 0.95 using PANDASEQ 35 .…”
Section: Sequence Processingmentioning
confidence: 99%
“…This includes the question how their components assemble, how they interact, how holobionts evolve, and what role they might play in speciation and macroevolution (Collens et al, 2019; Parker, Dury, & Moczek, 2019; Sevellec, Derome, & Bernatchez, 2018; Zilber‐Rosenberg & Rosenberg, 2008). Moreover, the very species studied by Meyer‐Abich are currently used again as model organisms to investigate the development and evolution of holobionts and other host‐microbiotes collectives: lichens (Aschenbrenner, Cernava, Berg, & Grube, 2016; Cernava et al, 2019), sponges (Pita, Fraune, & Hentschel, 2016; Webster & Thomas, 2016) and various plants, ranging from mosses, like Marchantia spp., to orchid species (Alcaraz et al, 2018; Hassani, Durán, & Hacquard, 2018; Jacquemyn, Waud, Merckx, Lievens, & Brys, 2015; Vandenkoornhuyse, Quaiser, Duhamel, Van, & Dufresne, 2015). Remarkably, current views of holobionts, both in evo‐devo and microbiology, share with Meyer‐Abich the assumption of the phylogenetic ubiquitous nature and evolutionary centrality of holobiosis (Gilbert, 2019; Gilbert et al, 2012; McFall‐Ngai et al, 2013; Rosenberg & Zilber‐Rosenberg, 2018).…”
Section: Discussionmentioning
confidence: 99%